2011
DOI: 10.1108/09596111111122497
|View full text |Cite
|
Sign up to set email alerts
|

RevPAR determinants of individual hotels

Abstract: PurposeThis paper aims to identify revenue per available room (RevPAR) determinants of individual firms located in a destination. Independent variables are to be sought along “what” and “where” dimensions.Design/methodology/approachThe sample is composed of 72 individual firms, operating in the 3‐5 star range and data have been collected from financial statements and questionnaires.FindingsThe empirical findings identify four main significant determinants linked to the “what” positioning – number of rooms, num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 72 publications
4
74
1
7
Order By: Relevance
“…Location-specific factors have so far received little attention in studies of the debt ratio of hotels and restaurants and related industries. For hotels, previous studies show that an ideal location is associated with higher hotel prices, higher performance, and a higher survival rate [25][26][27][28]. In the ski industry, the most important factors for performance and survival are the altitude of the terrain, size, and the presence of neighboring ski areas [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Location-specific factors have so far received little attention in studies of the debt ratio of hotels and restaurants and related industries. For hotels, previous studies show that an ideal location is associated with higher hotel prices, higher performance, and a higher survival rate [25][26][27][28]. In the ski industry, the most important factors for performance and survival are the altitude of the terrain, size, and the presence of neighboring ski areas [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Existen factores que afectan el RevPAR (Revenue Per Available Room) (Sainaghi, 2011) tales como la ubicación, la calidad (Zhang, Ye, & Law, 2011), la categoría, la tipología, la pertenencia a una cadena hotelera (Hernández, Fuentes, & Morini, 2012) o los comentarios publicados en la web (Anderson, 2012;Ye, Law, Gu, & Chen, 2011). La suma de información de un establecimiento publicada en la red se conoce como Reputación online, es decir, "la construcción social alrededor de la credibilidad, fiabilidad, moralidad y coherencia que se tiene de una persona, ente, organismo, institución o empresa, etc.…”
Section: Reputación Onlineunclassified
“…The findings reveal that large hotels produce higher sales revenues and net profits than do the small and medium properties. However, another study has found that the number of rooms is negatively correlated with the revenue per available room (RevPAR), as indicated by the results of Sainaghi (2011), who used individual hotels from Milan. He argued that smaller hotels are able to achieve a higher RevPAR.…”
Section: Introductionmentioning
confidence: 98%